2017
DOI: 10.5796/electrochemistry.85.174
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO Response of NASICON-based Gas Sensors Using Oxide-added Pt Sensing Electrode at Low Temperature Operation

Abstract: NASICON (Na 3 Zr 2 Si 2 PO 12 )-based solid electrolyte-type sensors equipped with various metal oxides (MO)-added Pt sensing electrode (SE, Pt(nMO) (n: MO additive amount in wt%) and Pt counter electrode (CE, Pt) on the same side of the NASICON disc were fabricated and their (Pt(nMO)/Pt sensors) CO-sensing properties were examined at 25-300°C. The Pt(15Bi 2 O 3 )/Pt sensor showed the largest CO response with a change in electromotive force to a positive direction (positive response) at 25°C, while the Pt(15Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The EC(CeO2) sensor showed the largest CO response (ΔECO: ca. 33 mV) among all the EC(MO) sensors, probably because of the relatively large electrocatalytic activity of CO oxidation over CeO2 [26]. However, the response and recovery speeds of the EC(CeO2) sensor were much slower than those of the EC(Bi2O3) sensor.…”
Section: Co-sensing Properties Of Ec(mo) Sensors and Effects Of Au Or...mentioning
confidence: 96%
“…The EC(CeO2) sensor showed the largest CO response (ΔECO: ca. 33 mV) among all the EC(MO) sensors, probably because of the relatively large electrocatalytic activity of CO oxidation over CeO2 [26]. However, the response and recovery speeds of the EC(CeO2) sensor were much slower than those of the EC(Bi2O3) sensor.…”
Section: Co-sensing Properties Of Ec(mo) Sensors and Effects Of Au Or...mentioning
confidence: 96%
“…CeO 2 into the Pt-sensing electrode largely responds to CO toward the negative electromotive force and the electrochemical cell assembled with the Bi 2 O 3 /Pt and CeO 2 /Pt electrodes shows the largest CO response among this kind of sensors tested. 122) On the other hand, yttria-stabilized zirconia (YSZ) is very valuable as a solid electrolyte of the electrochemical gas sensors at higher temperatures, 123) and thus we have also developed some kinds of YSZ-based electrochemical gas sensors. Ueda et al have demonstrated that the YSZ-based electrochemical gas sensors with a columnarstructured Pr 0.1 Ce 0.9 O 2 (PCO) electrode fabricated by PLD showed a large toluene response which increased with an increase in the thickness at 500 °C as shown in Fig.…”
Section: Jcs-japanmentioning
confidence: 99%
“…counter electrode, respectively, followed by annealing at 700°C in air [3]. The change in electromotive force generated between two electrodes induced by the exposure of both two electrodes to CO or H 2 sample gases from base air was measured under different conditions.…”
Section: Figmentioning
confidence: 99%
“…We have so far been trying several approaches to improve toxic gas sensing properties. The present paper reports our recent research results on semiconductor NO 2 sensors fabricated with porous In 2 O 3 powder [1] and solid electrolyte CO sensors fabricated with an anion-conducting polymer [2] or NASICON [3].…”
Section: Introductionmentioning
confidence: 99%